The Commodification of Tranquillity: Sufism in the Lifestyle of Jakarta’s Urban Muslims - Muslihan Habib; Johan Wahyudhi (Lembaga Bale Literasi, 2025)
This article examines changes in Sufi practices in the lives of urban Muslims through three religious spaces in Jakarta: the Habib’s religious study circles in the Bukit Duri–Tebet area, the Habib Kwitang Assembly, and the Al-Hawi Assembly in Condet, East Jakarta. Building on the concept of the commodification of tranquillity, the research examines how Sufi values and practices interact with the rhythm of metropolitan life, consumer culture, and the urban population’s need for spiritual spaces. The research employs a sociological approach to religion using qualitative methods, including observation of majelis activities, interviews with congregants and organisers, and an analysis of da’wah materials and social practices developing around the study circles. The research findings indicate that urban Sufism does not develop by distancing congregants from modern life. The practices of zikr, selawat, religious study sessions, and veneration of the figure of the habib coexist alongside work, mobility, consumption, and the digital lives of Jakarta’s residents. The need for tranquillity also brings spiritual experiences into contact with elements of lifestyle and economic activity, as evidenced using digital media, the appearance of congregants, religious products, and commercial activities around the majelis. Nevertheless, commodification does not automatically eliminate the religious function of these gatherings. These three spaces continue to serve as places where congregants can take a break from the pressures of city life, forge social bonds, and navigate the relationship between piety and worldly life. This research demonstrates that urban Sufism thrives through its ability to adapt spiritual tranquillity is not sought by abandoning metropolitan life, but rather by bringing religious experiences into the midst of everyday urban life.